Persepsi Masyarakat Tentang Kinerja Komisi Pemilihan Umum Dalam Pemilu 2024 di Kecamatan Benowo Kota Surabaya - Eriek Rahmat Kuncoro; Shobirin Noer; Hudallah Hudallah (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
Elections serve as a crucial pillar of democracy, allowing citizens to participate in the selection of leaders and shaping national policies. In Indonesia, the General Election Commission (KPU) is responsible for organizing elections, ensuring that the process is transparent, fair, and accountable. Understanding public perceptions of the KPU's performance is vital for evaluating the success and legitimacy of the democratic process, particularly in regions like Benowo District, Surabaya, which reflects the broader dynamics of local democracy. This study employs a qualitative methodology to explore and interpret the views and experiences of the public regarding the KPU's performance in the 2024 Election. Data were gathered through in-depth interviews with community leaders and direct observation of the election process. The qualitative approach allows for a comprehensive analysis of the complex and nuanced perceptions held by the community. The findings reveal that the public in Benowo District generally holds a positive perception of the KPU's performance, appreciating the orderliness, transparency, and efficiency of the electoral process. However, challenges such as logistics management were identified, indicating areas where the KPU can improve in future elections. These insights are crucial for enhancing the quality of electoral administration and strengthening the democratic process in Indonesia.